Evolution of holocene depositional environments in the coastal area from the Tien river to the Hau river mouths - Nghi, Tran; Dy, Nguyen Dich; Lam, Doan Dinh; Thanh, Dinh Xuan; Thai, Nguyen Dinh; Nhan, Tran Thi Thanh; Chi, Giap Thi Kim; Trang, Nguyen Thi Huyen (VNU Journal of Science: Earth and Environmental Sciences; Vol 26 No 4, 2010)
Abstract. The Holocene coastal zone o f Mekong river plain is the result o f prolonged marinefluvial interaction. Lithofacies association in time and space IS characterized by three depositional system ưact belonged to the upper part o f a sequence sưatigraphy. Based on lithology should be divided 5 sedimentary types and 18 lithofacies distributed in stratigraphical colum n and in sea bottom varying from 25m water depth to mainland coastal area. A ccording to sequence stratigraphy the ưansgressive systems tract at 5 Ky Bp, while from geochronology point o f view the boundary between Middle Holocene and Late H olocene is 3 Ky Bp - a regressive stage. During Early-Middle Holocene stage ưansgressive depositional system tract is characterized by two associated lilhofacies upward section: delta front swamp mud rich in organic materials facies and marine shallow grey-greenish clay facies corresponded with marine flooding plain. And then Late Holocene regressive phase corresponding with Highstand system s tract com posed o f delta plain clayish Slit facies in which there are different sandy ndges generations distributed younger seaward. Each sand ridge generation was mark by a coastal zone and associated lithofacies. In circumstance o f global climate change and sea-leve! rising, the M ekong river coastal zone will be changed much more in framework o f modem tectonic subsidence. If the rate o f sea-level rising is 2mm/ycar then sea bed will be subsided with a rate o f 4mm/year. But recent rate o f sediment accumulation is over 4mm/year, so the modem coastline continue to prograde seaward with a rate o f 40m/year. The Mekong river mouths are migrating to East-North, and as a result geosystems and landscapes arc changing.